TATA-binding protein and the retinoblastoma gene product bind to overlapping epitopes on c-Myc and adenovirus E1A protein. - Hateboer, G (1993)
Using a protein binding assay, we show that the amino-terminal 204 amino acids of the c-Myc protein interact directly with a key component of the basal transcription factor TFIID, the TATA box-binding protein (TBP). Essentially the same region of the c-Myc protein also binds the product of the retinoblastoma gene, the RB protein. c-Myc protein coimmunoprecipitates with TBP in lysates of mammalian cells, demonstrating that the proteins are also complexed in vivo. A short peptide that spans the RB binding site of the E7 protein of human papilloma virus type 16 interferes with the binding of c-Myc to TBP. The same peptide also blocks binding of adenovirus E1A protein to TBP, suggesting that c-Myc and E1A bind to RB and TBP through overlapping epitopes. Furthermore, we show that binding of RB to E1A prevents association of E1A with TBP. Our data suggest that one of the functions of RB and RB-like proteins is to prevent interaction of viral and cellular oncoproteins, such as c-Myc and E1A, with TBP.